Adherence to the mediterranean diet and lymphoma risk in the european prospective investigation into cancer and nutrition. Issue 1 (5th February 2019) - Solans, Marta; Benavente, Yolanda; Saez, Marc; Agudo, Antonio; Naudin, Sabine; Hosnijeh, Fatemeh Saberi; Noh, Hwayoung; Freisling, Heinz; Ferrari, Pietro; Besson, Caroline; Mahamat‐Saleh, Yahya; Boutron‐Ruault, Marie‐Christine; et al.
Abstract : There is a growing evidence of the protective role of the Mediterranean diet (MD) on cancer. However, no prospective study has yet investigated its influence on lymphoma. We evaluated the association between adherence to the MD and risk of lymphoma and its subtypes in the European Prospective Investigation into Cancer and Nutrition (EPIC) study. The analysis included 476, 160 participants, recruited from 10 European countries between 1991 and 2001. Adherence to the MD was estimated through the adapted relative MD (arMED) score excluding alcohol. Cox proportional hazards regression models were used while adjusting for potential confounders. During an average follow‐up of 13.9 years, 3, 136 lymphomas (135 Hodgkin lymphoma [HL], 2, 606 non‐HL and 395 lymphoma not otherwise specified) were identified. Overall, a 1‐unit increase in the arMED score was associated with a 2% lower risk of lymphoma (95% CI: 0.97; 1.00, p‐trend = 0.03) while a statistically nonsignificant inverse association between a high versus low arMED score and risk of lymphoma was observed (hazard ratio [HR]: 0.91 [95% CI 0.80; 1.03], p‐trend = 0.12). Analyses by lymphoma subtype did not reveal any statistically significant associations. Albeit with small numbers of cases ( N = 135), a suggestive inverse association was found for HL (HR 1‐unit increase = 0.93 [95% CI: 0.86; 1.01], p‐trend = 0.07). However, the study may have lacked statistical power to detect small effect sizes for lymphoma subtype. Our findings suggest that an increasing arMED score was inversely related to the risk of overall lymphoma in EPIC but not by subtypes. Further large prospective studies are warranted to confirm these findings. Abstract : What's new? Known risk factors explain only a small proportion of lymphoma cases. Several studies have pointed out the potential role of dietary factors on lymphoma risk, but evidence is still inconclusive. Here, using data from the European Prospective Investigation into Cancer and Nutrition study, the authors found for the first time that adherence to a Mediterranean diet was modestly associated with a reduced risk of overall lymphoma. Further studies are needed to confirm these findings.